A reductively treated thin layer MoS2 nanosheet-poly(xanthurenic acid) composite with dramatically enhanced electrochemical performance and extended sensing applications. (1st February 2016) - Wang, Xinxing; Ma, Wenqing; Ge, Tong; Yang, Tao; Jiao, Kui
Graphical abstract: Highlights: A reductively treated thin layer MoS2 nanosheet-poly(xanthurenic acid) (rTLMoS2 -PXa) composite was fabricated by simple one-step electrosynthesis. The obtained rTLMoS2 -PXa composite possesses dramatically enhanced electron transfer capability and enlarged surface area. The enhanced electrochemical performance of the composite leads to its good sensing performance towards dGTP, BPA and TNT. The three analytes have never or rarely been analyzed by MoS2 -based sensing platform. This research further extends the application of MoS2 in the field of electrochemical sensing. Abstract: Polymer inorganic nanosheet composites hold great promise in electrochemical sensing applications by improving the electrochemical performance and increasing the surface area. In this work, a reductively treated thin layer molybdenum disulfide nanosheet-poly(xanthurenic acid) (rTLMoS2 -PXa) composite have been facilely prepared through a one-step electrosynthesis procedure. The TLMoS2 was used as building block for the construction of the composite with the PXa coated on it. The composite modified electrode possesses improved electron transfer capability and exhibits good electrochemical sensing performance towards several heterocyclic and aromatic ring compounds (2′-deoxyguanosine-5′-triphosphate trisodium salt, dGTP, bisphenol A, BPA and 2, 4, 6-trinitrotoluene, TNT), which have good affinity to the electroactive PXa and never or rarely been analyzed by MoS2 -based sensing platform. This research provides a new electrochemical sensing platform for simple and sensitive detection of dGTP, BPA and TNT, and further extends the application of MoS2 in the field of electrochemical sensing.